Association of Lesion Pattern and Dysphagia in Acute Intracerebral Hemorrhage. Issue 9 (18th May 2021) - Hess, Felix; Foerch, Christian; Keil, Fee; Seiler, Alexander; Lapa, Sriramya
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Dysphagia is a common and severe symptom of acute stroke. Although intracerebral hemorrhages (ICHs) account for 10% to 15% of all strokes, the occurrence of dysphagia in this subtype of stroke has not been widely investigated. The aim of this study was to evaluate the overall frequency and associated lesion locations and clinical predictors of dysphagia in patients with acute ICH. Methods: Our analysis included 132 patients with acute ICH. Clinical swallowing assessment was performed within 48 hours after admission. All patients underwent computed tomography imaging. Voxel-based lesion-symptom mapping was performed to determine lesion sites associated with dysphagia. Results: Eighty-four patients (63.6%) were classified as dysphagic. Higher scores on the National Institutes of Health Stroke Scale, larger ICH volumes, and higher degree of disability were associated with dysphagia. Voxels showing a statistically significant association with dysphagia were mainly located in the right insular cortex, the right central operculum, as well as the basal ganglia, corona radiata, and the left thalamus and left internal capsule. In contrast to lobar regions, in subcortical deep brain areas also small lesion volumes (<10 mL) were associated with a substantial risk of dysphagia. Intraventricular ICH extension and midline shift as imaging findings indicating a space-occupying effect were not associated with dysphagia in multivariate analysis. Conclusions: Dysphagia is a frequent symptom in acute ICH. Distinct cortical and subcortical lesion sites are related to swallowing dysfunction and predictive for the development of dysphagia. Therefore, patients with ICH should be carefully evaluated for dysphagia independently from lesion size, in particular if deep brain regions are affected.